In-Hospital Outcomes Following Extracorporeal Membrane Oxygenation in a Retrospective Cohort of Infants - Schueller, Maya; Greenberg, Rachel G.; Smith, P. Brian; Laughon, Matthew M.; Clark, Reese H.; Hornik, Christoph P. (American Journal of Perinatology, 2017)
Objective We sought to characterize associations between infant characteristics and extracorporeal membrane oxygenation (ECMO) survival using electronic health records data.Study Design We examined a cohort study of infants ≥32 weeks of gestational age and ≥1,800 g birth weight supported with ECMO in a Pediatrix Medical Group neonatal intensive care unit from 1998 to 2013.Results We identified 268 infants, of which 45 (17%) were <37 weeks of gestational age. Survival to discharge was 87% but was lower in premature compared with term infants (76 vs. 89%, p = 0.03). In multivariable analysis, acute kidney injury (odds ratio [OR] = 4.00; 95% confidence interval [CI] = 1.05, 15.24), postnatal age at cannulation of 7 to 13 days (OR = 5.86; 95% CI = 1.21, 28.44), and venoarterial ECMO cannulation (OR = 4.33; 95% CI = 1.77, 10.60) were associated with lower survival.Conclusion ECMO cannulation type, postnatal age, and acute kidney injury were associated with lower ECMO survival, while prematurity was not. Future studies are needed to identify risk factors and strategies to improve outcomes.
Keywords: extracorporeal membrane oxygenation; infant; survival; temporal trends